Thermal and Structural Analysis of Airborne Magnetic Data of part of Nasarawa State, Nigeria: Implication for Geothermal Energy Exploration (Lafia Journal of Scientific and Industrial Research, 2024)
This study presents the results of thermal and structural analysis of airborne magnetic data of part of Nasarawa State, Nigeria. The study area is characterised by a complex geological setting, with numerous faults and fractures that may control geothermal activity. The Total Magnetic Intensity (TMI) of the study area was analysed using various techniques, including spectral analysis, Analytic signal (AS), Center for Exploration Targeting (CET), First vertical derivative (FVD), and second vertical derivative (SVD). The results of the CET, FVD, and SVD reveal a complex geological structural pattern, with numerous faults and fractures that may be related geothermal activity, trending majorly NE-SW direction. The AS map distinguished regions of high, intermediate, and low amplitude anomalies within the study area. The thermal analysis evaluated Curie point depth (CPD), geothermal gradient (GG), and heat flow (HF). Estimated values of CPD, GG, and HF range from 10 to 22.65 km, 25 to 55 °C/km, and 60 to 140 mW/m2, respectively. Feasible HF for geothermal resources were observed at the mid-portion of the northern region, corresponding to Mada, Nasarawa Egon, Akwanga, and at the western and south-eastern edges, covering Udeni and Keana. The delineated major structures in NE-SW direction might serve as migration conduits and channels for crustal HF within the study area. The results of this study have significant implications for geothermal exploration in the study area, and suggest that further investigation is warranted to determine the feasibility of geothermal energy production.
Keywords: Geothermal energy; heat flow; Curie point depth; renewable energy